Effect of particle size of zeolite clay included in high-energy diets for feedlot lambs: Growth performance, dietary energy, carcass traits, and visceral mass (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: Several reports on the effects of zeolite (ZEO) inclusion in diets for feedlot lamb diets have indicated improvements in dietary energy efficiency and decreases in internal fat. Inclusion levels and the type of zeolite used have been the main focus of those reports. However, the possible effect of the zeolite particle size on the growth performance and carcass characteristics has not yet been investigated. Material and Methods: Forty-eight male intact Pelibuey × Katahdin lambs were fed for 67 days with a high-energy diet supplemented with ZEO as follows: 1) basal diet 0% ZEO (control); 2) basal diet 3% ZEO particle size 250 µM (sieve 60); 3) basal diet 3% ZEO particle size 149 µM (sieve 100); and 4) basal diet 3% ZEO particle size 74 µM (sieve 200). ZEO replaced corn grain and soybean meal in equal parts. At the end of feeding, lambs were slaughtered, and variables such as carcass characteristics and visceral mass were evaluated. Results: Particle size did not affect growth performance, carcass characteristics, or visceral mass. The inclusion of ZEO reduced 3.4% of dietary net energy in diets but did not affect dry matter intake or average daily gain, thus improving (p ≤ 0.05) dietary energy efficiency by 2.9%. Except for an 18.9% reduction (p = 0.02) in visceral mass fat, ZEO did not affect other carcass characteristics or visceral organ mass. Conclusion: The particle size studied in the present experiment has not affected any of the variables of growth performance or carcass characteristics. ZEO inclusion could be a strategy to reduce the visceral fat in finishing lambs.J. Adv. Vet. Anim. Res., 10(3): 500–506, September 2023http://doi.org/10.5455/javar.2023.j703